Dissenting Voices: When Paratexts Clash With Texts. Paratextual Intervention in Persian Translations of Texts Relating to the Iran-Iraq War - Yalsharzeh, Reza; Barati, Hossein; Hesabi, Akbar (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
This study uses narrative theory and the concept of narrative framing, as elaborated by Somers and Gibson (1994) and Baker (2006), to study the paratextual mediation and discursive presence of different agents in Persian translations of political texts written by Western authors about the Iran-Iraq war. By exploring the narratives dominant in the paratexts, and more specifically in the prefaces and footnotes of Persian translations, this paper examines how these have played a crucial role in reframing the narratives of Western authors through paratextual material. To this end, the narratives in the paratexts have been analyzed using four framing techniques elaborated by Somers and Gibson (1994) and Baker (2006), which are framing by temporality/spatiality, selective appropriation, labeling and participant positioning. The analysis of paratextual material shows that, apart from their introductory and explanatory functions, paratexts can be viewed as a kind of metadiscourse on the actual translations. The paper concludes that paratexts in the Persian translations are used in political and ideological ways to guide target language readers and to express the appropriate interpretations, or deemed appropriate, by the various institutional participants involved in the translation process in Iran.